From Knowledge to Practice: Investigating the TPACK Integration of Indonesian Pre-Service EFL Teachers - Rakerda, Hilda; Lathif, Masyhudi; Amalia, Resti; Bowo, Tri Arie; Afandi, Rizky Arif (Universitas Hamzanwadi, 2025)
Effective technology integration in English as a Foreign Language (EFL) teaching requires teachers to develop strong Technological Pedagogical Content Knowledge (TPACK). In Indonesia, where teacher education programs increasingly emphasize digital learning, understanding pre-service EFL teachers’ self-concept of TPACK is crucial for assessing their readiness before entering the profession. This study examines the TPACK profile of Indonesian pre-service EFL teachers, identifying their strengths and areas for improvement in applying technology to language instruction. The study involved 111 final-year undergraduate and first-year master's students who had completed teaching practice but had no formal teaching experience. Data were collected using a TPACK survey and analyzed through descriptive statistics to identify patterns in their TPACK mastery. Findings reveal that pre-service teachers are confident in their content knowledge (CK) and basic technological skills (TK). Still, they struggle with the full integration of technology into pedagogy (TPK), pedagogical adaptability (PK), and leadership in TPACK. While they acknowledge the importance of technology in teaching, gaps persist in their ability to select and apply diverse technologies effectively in classroom settings. Additionally, they face challenges adapting teaching strategies to different learners and assessing student understanding in varied ways. Their leadership in supporting peers with TPACK integration was also limited. These insights underscore the need for curricular enhancements in teacher education programs at both undergraduate and postgraduate levels, focusing on practical applications of TPACK, deeper technological and pedagogical training, and leadership development to better prepare future EFL educators for technology-enhanced instruction.